Distribusi dan diversitas genetik bakteri diazotrof endofit pada tanaman tebu(Saccharum officinarum L)=Distribution and genetic diversity of diazotrhropic Endophytes in ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ARDRA (Amplified rDNA Restriction Analysis) has been widely used to provide a relatively quick and simple analysis of microbial community diversity and phylogenetic relationship. A study has been carried out to determine the distribution and genetic diversity of diazotrophic endophytes in sugarcane root, stem, and leaves tissues using the ARDRA methodology based upon PCR (Polymerase Chain Reaction) amplification and RFLP (Restriction Fragments Length Polymorphism) analysis. Bacterial endophytes were isolated from sugarcane root, stem, and leaves tissues, followed by screening of diazotrophic bacteria using ARA (Acetylene Reduction Assay) analysis. The 16S rDNA was then PCR-amplified from the genomes of diazotrophic bacteria, followed by restriction enzyme analysis to create dendograms calculated based upon Dice Coefficient and UPGMA algorithm. The result of analysis demonstrated that eleven isolates of diazotrophic bacterial endophytes were distributed troughout root, stem, and leaves of sugarcane. The use of three different restriction enzymes, i.e. HaeIII, Hinfl, and RsaI was found to be sufficient in distinguishing the diversity among the isolates of diazotrophic bacterial endophytes. The dendogram produced based upon restriction enzyme analysis demonstrated no similarity between diazotrophic bacterial endophytes and thereference strains, i.e. either Azorhizophilus paspali DSM 2283T or â¢ Azotobacter chroococcum DSM 2286T. Similarity index produced was in the range of 0-100%. The highest similarity index (100%) was found among isolates ra9 and rbb9. It was assumed that the two isolates were the same and were found distributed in root and stem of sugarcane. Similarly, isolates ra12 and rdb12 also had 100% similarity index and were distributed in root and leaves of sugarcane.